pneumonia in pediatric patients: an analysis of 15 confirmed consecutive cases during 14 years - Kyung-Ran Kim; Jong Min Kim; Ji-Man Kang; Yae-Jean Kim (Korean Pediatric Society, 2016)
PurposePneumocystis jirovecii pneumonia occurs in various immunocompromised patients. Despite the prophylaxis strategies in clinical practice, certain patients develop P. jirovecii pneumonia. This study was performed to investigate pediatric cases with P. jirovecii pneumonia in a single center.MethodsWe identified pediatric patients younger than 19 years with microbiologically confirmed P. jirovecii pneumonia from January 2000 to February 2014. A retrospective chart review was performed.ResultsFifteen episodes of P. jirovecii pneumonia in 14 patients were identified with median age of 8.3 years (range, 0.4-18.6 years). Among these patients, 11 patients had hematology-oncology diseases, 2 had primary immunodeficiency disorders (one with severe combined immunodeficiency and the other with Wiskott Aldrich syndrome), 1 had systemic lupus erythematosus and 1 received kidney transplant. Four patients were transplant recipients; 1 allogeneic and 2 autologous hematopoietic cell transplant and 1 with kidney transplant. The median absolute lymphocyte count at the diagnosis of P. jirovecii pneumonia was 5,156 cells/mm3 (range, 20-5,111 cells/mm3). In 13 episodes (13 of 15, 86.7%), patients were not receiving prophylaxis at the onset of P. jirovecii pneumonia. For treatment, trimethoprim/sulfamethoxazole was given as a main therapeutic agent in all 15 episodes. Steroid was given in 9 episodes (60%). Median treatment duration was 15 days (range, 4-33 days). Overall mortality at 60 days was 35.7% (5 of 14).ConclusionMajority of our patients developed P. jirovecii pneumonia while not on prophylaxis. Continuous efforts and more data are needed to identify high risk patients who may get benefit from P. jirovecii pneumonia prophylaxis.